RAF gene fusion breakpoints in pediatric brain tumors are characterized by significant enrichment of sequence microhomology - Lawson, Andrew R.J.; Hindley, Guy F.L.; Forshew, Tim; Tatevossian, Ruth G.; Jamie, Gabriel A.; Kelly, Gavin P.; Neale, Geoffrey A.; Ma, Jing; Jones, Tania A.; Ellison, David W.; Sheer, Denise (Genome Research, 2011)
Gene fusions involving members of the RAF family of protein kinases have recently been identified as characteristic aberrations of low-grade astrocytomas, the most common tumors of the central nervous system in children. While it has been shown that these fusions cause constitutive activation of the ERK/MAPK pathway, very little is known about their formation. Here, we present a detailed analysis of RAF gene fusion breakpoints from a well-characterized cohort of 43 low-grade astrocytomas. Our findings show that the rearrangements that generate these RAF gene fusions may be simple or complex and that both inserted nucleotides and microhomology are common at the DNA breakpoints. Furthermore, we identify novel enrichment of microhomologous sequences in the regions immediately flanking the breakpoints. We thus provide evidence that the tandem duplications responsible for these fusions are generated by microhomology-mediated break-induced replication (MMBIR). Although MMBIR has previously been implicated in the pathogenesis of other diseases and the evolution of eukaryotic genomes, we demonstrate here that the proposed details of MMBIR are consistent with a recurrent rearrangement in cancer. Our analysis of repetitive elements, Z-DNA and sequence motifs in the fusion partners identified significant enrichment of the human minisatellite conserved sequence/χ-like element at one side of the breakpoint. Therefore, in addition to furthering our understanding of low-grade astrocytomas, this study provides insights into the molecular mechanistic details of MMBIR and the sequence of events that occur in the formation of genomic rearrangements.
10.1101/gr.115782.110